Desplazamiento activo y trastornos del sueño en estudiantes universitarios del primer semestre de la facultad de ciencias políticas - Yungán Aguirre, Darío Javier (2019)
The research project related to the development of active displacement and sleep disorder in students of the first semester of the Faculty of Political Sciences, had as specific objective the active displacement and sleep disorder in university students. The population was composed of students of the first semesters of the different careers in the Political Sciences faculty at the National University of Chimborazo, with an intentional sample of 172 young people conformed by 103 women and 69 men between the ages of 18 to 25 years. In this age group, the present investigation has a non-probabilistic sample, with a quasi-experimental model, a transversal design and a qualitative quantitative type. The survey with the instrument called Questionnaire on Active Displacement and Sleep Disorder was used as a research technique. It was obtained as a result that the ways of moving of the majority of the students surveyed at the National University of Chimborazo are passively, 60% of students move by car, bus or motorcycle and with low percentages actively walking or by bicycle completing 100% of the studied percentage. In terms of sleep, the average sleep hours and the different sleep disorders showed regular results, wich mean the time in average hours of sleep are from 6 to 7 hours from Monday to Friday and 8 sleep hours at weekends and most students had problems falling asleep, concluding that students do not perform any physical activity that promotes a good quality of life and that most of the population are passive when moving to university, throwing results that show problems of sleep disorders.